KARAKTERISTIK KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN ISLAM TRADISIONAL DAN MODERN - Khoirunnisaa' Khoirunnisaa'; Binti Maunah (MANAGERE : Indonesian Journal of Educational Management, 2021)
This paper aims to analyze transformational leadership characteristics in traditional and modern Islamic educational institutions by referring to four transformational features: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The method used is a qualitative method with a library research approach. Inductive data analysis describes data from facts and the field associated with the theory. Sources of data used are the results of literature from books and journals. The results of the study show that the characteristics of transformational leadership in the Salaf and modern Islamic boarding schools, among others; 1) Build creative ideas through vision and mission to achieve goals, become role models, and influence subordinates through their behavior and charisma; 2) Provide inspiration and motivation through a clear vision; 3) encourage subordinates to find practical ideas in solving problems; 4) understand and appreciate subordinates based on needs and pay attention to the desire to achieve and develop.